Marriage Markets in Developing Countries - S Anukriti; Shatanjaya Dasgupta (Institute of Labor Economics (IZA), 2017)
This chapter reviews the literature on marriage in developing countries. We describe how marital matching occurs; the trends in age at marriage; assortative mating patterns; marriage payments; and spousal decision-making after a marriage has occurred. Lastly, we discuss trends and rationales for consanguineous and polygamous marriages practices that are largely unique to the developing world.
Keywords: J1; J12; 330; marriage; developing countries; marriage markets